Simulating toponium formation signals at the LHC - Benjamin Fuks; Kaoru Hagiwara; Kai Ma; Ya-Juan Zheng (European Physical Journal C: Particles and Fields)
Abstract We present a method to simulate toponium formation events at the LHC using the Green’s function of non-relativistic QCD in the Coulomb gauge, which governs the momentum distribution of top quarks in the presence of the QCD potential. This Green’s function can be employed to re-weight any matrix elements relevant for $$t{\bar{t}}$$ t t ¯ production and decay processes where a colour-singlet top–antitop pair is produced in the S-wave at threshold. As an example, we study the formation of $$η _t$$ η t toponium states in the gluon fusion channel at the LHC, combining the re-weighted matrix elements with parton showering.